Attitude toward gender inequality in China - Qianqian Wang; Tsun-Feng Chiang; Jing Jian Xiao (Humanities & Social Sciences Communications, 2024)
Abstract This study explores determinants of attitudes toward gender inequality among Chinese people using five waves of the Chinese General Social Survey (CGSS) and East Asian Social Survey (EASS, 2016). The study uses five survey questions regarding the relative roles of men and women in the family and workplace to measure gender attitudes. Utilizing the pooled data, the study finds temporal changes of attitude: women are expected to be more responsible for paid jobs than before while their job security is not given enough support; meanwhile, women’s share in housework is not anticipated to be reduced. The results suggest that the Chinese attitude toward women’s roles is stuck between the modern and old eras. Education is found to be the most crucial determinant of attitude. Education is positively correlated with attitudes supporting women regarding gender inequality. In addition, if the wife has a higher education than the husband, the respondent tends to have an attitude toward gender equality. Furthermore, a large part of the urban-rural difference in attitude can be explained by the urban-rural difference in education. These findings have a straightforward policy implication: to reduce the negative attitude toward gender inequality, education for women and rural regions needs to be promoted. Additionally, by combining the Chinese General Social Survey 2017 and the East Asian Social Survey 2016, this study finds that an individual’s patrilineal values conflict with the attitude toward gender equality, suggesting that traditional culture is a potential root of gender inequality.